THE INFLUENCE OF THE BLENDED LEARNING MODEL ON CIVICS LEARNING OUTCOMES AT NURUL ISLAM INDONESIA HIGH SCHOOL FOR THE 2022/2023 ACADEMIC YEAR - azwan, Muhammad; Husna, Muhammad Faisal (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
This research is experimental research using the "One Group Pretest-posttest Design" research design. The aim of this research is to determine whether or not there is an influence of the Blended Learning learning model on PPKn learning outcomes in class XI students at SMA Nurul Islam Indonesia. The collected data was then analyzed using descriptive statistical techniques and inferential statistics (t test/t-count). Based on the results of data analysis, it appears that there is an influence of using the Blended Learning model on PPKn learning outcomes for class XI students at Sma Nurul Islam Indonesia with a value obtained t = 21.905. Based on the tcount value, it can be compared with the ttable value df = N – 1 = 20 – 1 = 19, then we get ttable = 1.729 (significance 0.05). So we get t count > t table or 21.905 > 1.729. So it can be concluded that Ho is rejected and Ha is accepted. So it can be concluded that there is an influence of the use of the Blended Learning learning model on Civics learning outcomes in class XI IPS1 students at SMA Nurul Islam Indonesia Medan